The use of circular economy practices in SMEs across the EU - Bassi, F.; Dias, J. G. (Resources, Conservation and Recycling, 2019)
This study explores the circular economy (CE) practices of Small and Medium Enterprises (SMEs) in the 28 European Union (EU) member states. Five measures of CE are studied, namely Re-planning the way water is used to minimize usage and maximize re-usage, Using renewable energy, Re-planning energy usage to minimize consumption, Minimizing waste by recycling or reusing waste or selling it to another firm, and Redesigning products and services to minimize the use of materials or using recycled materials. Multilevel ordinal probit models that control within- and between-variability across European Union countries are estimated. Results show that CE measures across EU countries are very heterogeneous. At the firm level, we find that firm size (number of employees and total turnover in 2015) and percentage of firms’ turnover invested in R&D in 2015 are significant in explaining within-country variations. The multilevel structure (between-country variability) accounts for 6.1%–15.1% of the total variability of CE measures. These results have implications for the design of framework policies at EU level given that the firms surveyed are SMEs, the segment in which these CE measures most need improved planning and implementation.